Transformaç\~oes recentes da indústria no Sudeste: Evidências da dinâmica produtiva e territorial entre 1996 e 2015 - Raphael de Oliveira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The present study aims to investigate the transformations in industrial activity in three states of the Southeast region (S\~ao Paulo, Rio de Janeiro and Minas Gerais), the significant nucleus of Brazilian industry, between 1996 and 2015, with a focus on change structural and territorial reorganization. By means of the descriptive statistics of a set of indicators, according to the predominant competitive factor of the industrial activity, it was possible to verify that, in general lines, the region did not show retrocession in the industrial activity, since, there was no decrease in absolute terms of the production and/or industrial employment. But, the low growth rates of the industry in the region; structural change with the expansion of traditional industry, to the detriment of the scale-intensive industry; and the reduction of productive densities - with the exception of activities based on natural resources - signalize harmful aspects of their dynamics. Within the territorial scope, deconcentration is notorious in all sectoral categories analyzed, even in a context of semi-stagnation of industry.
Keywords: L60; O14; R11; 330; regional development; structural change; regional deconcentration